2020
DOI: 10.1002/ece3.6516
|View full text |Cite
|
Sign up to set email alerts
|

Assessing biotic and abiotic effects on forest productivity in three temperate forests

Abstract: It is well understood that biotic and abiotic variables influence forest productivity. However, in regard to temperate forests, the relative contributions of the aforementioned drivers to biomass demographic processes (i.e., the growth rates of the survivors and recruits) have not received a great deal of attention. Thus, this study focused on the identification of the relative influencing effects of biotic and abiotic variables in the demographic biomass processes of temperate forests. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
2
9
1
Order By: Relevance
“…In addition, the relationship between species richness (or phylogenetic diversity) and biomass was not statistically signi cant when other factors were accounted for in the multiple regression model (Fig. 3a), indicating that species richness and phylogenetic diversity have independent effects on biomass, which is consistent with previous studies in temperate forests (Fotis et al 2017;Yue et al 2020). Linear regression analysis revealed that species richness and phylogenetic diversity are a better predictor of biomass that functional diversity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the relationship between species richness (or phylogenetic diversity) and biomass was not statistically signi cant when other factors were accounted for in the multiple regression model (Fig. 3a), indicating that species richness and phylogenetic diversity have independent effects on biomass, which is consistent with previous studies in temperate forests (Fotis et al 2017;Yue et al 2020). Linear regression analysis revealed that species richness and phylogenetic diversity are a better predictor of biomass that functional diversity.…”
Section: Discussionsupporting
confidence: 88%
“…Tree size inequality is caused by both differences with and among species and represents niche differentiation and facilitation (Coomes et al 2009; Morin et al 2011), a key process for maintaining species diversity and the positive diversity-productivity relationships. Together with previous studies, furthermore, we have demonstrated that the positive impact of stand density on forest biomass in natural forest ecosystems (van der Sande et al 2017; Yuan et al 2018;Yue et al 2020). Stand density can re ect the available resources and space occupation of trees and may also, to some extent, re ect intraspeci c interactions (Morin 2015;Fortunel et al 2018).…”
Section: Stand Structure As Predictors Of Forest Biomasssupporting
confidence: 80%
“…Biological dissimilarities have been widely used in multiple areas of forest ecological research, such as examining community assembly mechanisms (Swenson & Enquist, 2009; Kraft & Ackerly, 2010; Spasojevic & Suding, 2012), exploring vegetation evolutionary processes (Bouchenak‐Khelladi et al, 2010; Byrne & Murphy, 2020), and assessing the relationship between biodiversity and ecosystem functioning (Tilman et al, 1997; Paquette & Messier, 2011; Finegan et al, 2015; Hao et al, 2018, 2020; Yue et al, 2020). Some previous studies have attempted to incorporate biological attributes into vegetation classifications.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially relevant in global assessments, for example, when forest vegetation data are collected from large-scale forest inventories. Murphy, 2020), and assessing the relationship between biodiversity and ecosystem functioning (Tilman et al, 1997;Paquette & Messier, 2011;Finegan et al, 2015;Hao et al, 2018Hao et al, , 2020Yue et al, 2020). Some previous studies have attempted to incorporate biological attributes into vegetation classifications.…”
Section: Classification Methods Used In This Studymentioning
confidence: 99%
See 1 more Smart Citation